2010
DOI: 10.1159/000276401
|View full text |Cite
|
Sign up to set email alerts
|

Perforator Territory Infarction in the Lenticulostriate Arterial Territory: Mechanisms and Lesion Patterns Based on the Axial Location

Abstract: Background: We hypothesized that perforator territory infarcts in the lenticulostriate territory (pLSAIs) may have heterogeneous lesion patterns and stroke mechanisms. Methods: We reviewed prospectively collected patients who developed pLSAIs within 72 h after stroke onset. Lesion patterns were analyzed based on the six axial levels. Based on MR angiography, stenosis of the middle cerebral artery (MCA) was classified into 3 groups. White matter hyperintensities were assessed by Fazeka’s scale of periventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 87 publications
2
14
0
Order By: Relevance
“…These results are consistent with previous studies reporting that dSSI is more often associated with the characteristics of small-vessel disease than pSSI. 5,6 In addition, we found that as many as 51.3% of patients with SSI demonstrated HR-MRI-identified MCA plaques, even if the patient's MRA findings were normal. This result agrees with recent studies reporting that MCA plaques are present in 42% to 60% of patients with lacunar infarction.…”
Section: Strokementioning
confidence: 72%
See 1 more Smart Citation
“…These results are consistent with previous studies reporting that dSSI is more often associated with the characteristics of small-vessel disease than pSSI. 5,6 In addition, we found that as many as 51.3% of patients with SSI demonstrated HR-MRI-identified MCA plaques, even if the patient's MRA findings were normal. This result agrees with recent studies reporting that MCA plaques are present in 42% to 60% of patients with lacunar infarction.…”
Section: Strokementioning
confidence: 72%
“…5 Previous studies have shown that dSSI is associated with the characteristics of small-vessel disease, including abundant microbleeds and white matter ischemic changes, whereas pSSI is more often associated with atherogenic characteristics, such as the concomitant presence of atherosclerotic cerebral vessels. 5,6 Recently, studies have reported that high-resolution MRI (HR-MRI) can show the vessel wall structure and, therefore, detect early atherosclerotic changes such as plaques, wall thickening, and arterial remodeling, even in patients with normal findings on magnetic resonance angiography (MRA). 7,8 Because the lesion characteristics of pSSI are similar to those of SSI associated with parental artery disease, 5 pSSI may be more closely associated with HR-MRI-identified MCA plaques than dSSI in patients who do not show parental artery disease on MRA.…”
mentioning
confidence: 99%
“…These results are consistent with previous studies. 1,4 For example, Cho et al 4 found that patients with dSSI had more severe white matter changes, and Nah et al 1 found that these patients had a higher prevalence of microbleeds and leukoaraiosis compared with patients with pSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the lowest portion of the basal ganglia was considered as an extension to the basal surface of MCA. 4 A diagram for the possible mechanisms of dSSI and pSSI is illustrated in Figure 2. The largest lesion was used to determine the volume of infarction: 1/2×diameter of length×diameter of width×numbers of MRI diffusion-weighted imaging slices of SSI.…”
Section: Mri Analysismentioning
confidence: 99%
See 1 more Smart Citation